2022
DOI: 10.1007/s00268-022-06795-4
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Adipose Tissue Content as a Predictor of Incisional Hernia after Hepatic Resection

Abstract: Background Incisional hernia (IH) is a common surgical complication, with an incidence of 6–31% following major abdominal surgery. This study aimed to investigate the impact of intramuscular adipose tissue content (IMAC) on the incidence of IH in patients who underwent hepatic resection. Methods Data of 205 patients who underwent open hepatic resection between 2007 and 2019 at Ehime University Hospital were retrospectively analyzed. Patient characteristics, perioperative findings, and body composition were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The present study used VFA, SFA, and IMAC as variables to measure patients' obesity, and these variables successfully predicted the development of IH after surgery. In contrast, BMI was not a predictor of IH development in multivariate analysis 8,9,16–21 . The incidence of IH development varied from 1.0% to 27% in the included studies, 8,9,16–21 which may be due to differences in the type of abdominal surgery, primary disease, location of defects, and fascia closure techniques used.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The present study used VFA, SFA, and IMAC as variables to measure patients' obesity, and these variables successfully predicted the development of IH after surgery. In contrast, BMI was not a predictor of IH development in multivariate analysis 8,9,16–21 . The incidence of IH development varied from 1.0% to 27% in the included studies, 8,9,16–21 which may be due to differences in the type of abdominal surgery, primary disease, location of defects, and fascia closure techniques used.…”
Section: Discussionmentioning
confidence: 91%
“…One study, conducted on 205 patients who underwent open hepatic resection, reported the impact of IMAC on the incidence of IH 16 . The author found that a high IMAC was an independent risk factor for IH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations